Identification the Highest Risk of Performance Based Contract in Bojonegoro-Padangan Road Projects - Eko Prihartanto; M. Djaya Bakri (IPTEK Journal of Proceedings Series, 2017)
Development of road facilities and infrastructure in order to meet the need to improve the welfare of the community. Contract of project activity is carried out to bind both parties in this case, Owner and contractor as an interested party has the purpose to bind the rights and responsibilities in completing project activities. Performance based contracts are the innovative contracts presented by the Indonesian government to improve the quality of construction of road construction. The risk of applying this type of contract will be investigated so that it will be known to the highest risk, given the performance based contract has 4  stages such as design, build, operate, and maintenance. The project that implements the performance based contract under study is the Bojonegoro-Padangan road project, East Java.  In the process of knowing the highest risk variable that occurs in the implementation, the researcher uses a simple probabilistic concept to determine the highest risk of each stage of a performance based contract. The correspondent of the contractor is PT Pembangunan Pembangunan (Persero) Tbk - PT Basuki Rahmanta Putra (Joint Operational) on the road construction project Bojonegoro – Padangan, East Java. The results obtained from this study from the implementation of performance-based contracts on the Bojonegoro-Padangan road construction project with the highest risk event gain is at the Design stage: Project budget. Build Stage: The vendor's offer price is higher than estimated. Operate Phase: Cashflow delay. Maintenance Stage: Short-term focus fails to minimize long-term costs.